Memorable Tourist Experience and Tourist Satisfaction: Implications for Revisit Intention in Kota Lama Surabaya Heritage Tourism - Rahmawati, Ita; Fadhli, Khotim; Fahimah, Mar'atul; Budi, Febrianto Setyo (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
This study aims to analyze the effect of Memorable Tourist Experience (MTE) on Revisit Intention with Tourist Satisfaction as a mediating variable in the heritage tourism destination of Kota Lama Surabaya. This study uses a quantitative approach with an associative causal research type. Data collection was conducted through an online questionnaire distributed to tourists who had visited Kota Lama Surabaya. The sampling technique used non-probability sampling with the snowball sampling method, resulting in 200 respondents. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Memorable Tourist Experience has a positive and significant effect on Tourist Satisfaction, Tourist Satisfaction has a positive and significant effect on Revisit Intention, and Memorable Tourist Experience has a positive and significant effect on Revisit Intention through Tourist Satisfaction. These findings confirm that memorable tourist experiences can increase satisfaction, which ultimately strengthens tourist loyalty to make repeat visits. This study has implications for urban heritage destination development strategies, particularly in creating authentic and meaningful experiences for tourists to enhance the competitiveness and sustainability of Kota Lama Surabaya.